(untitled) - Gul, Ferdinand A. (New York, 2004)
This book examines government/regulatory responses to the Asian financial crisis which brought unprecedented financial turmoil for most East Asian countries. It provides thought-provoking insights on fundamental differences in the institutional and regulatory framework of ten East Asian countries, including an assessment of the various corporate governance reforms after the crisis.
Keywords: Corporate governance,Corporate governance; East Asia,Southeast Asia